Second auditor's report on the internal improvements east and west of the Blue Ridge (House document (Virginia. General Assembly. House of Delegates), 1844)
1844 Second Auditor's report and supplemental report regarding the internal improvements on the east and west of the Blue Ridge, pursuant to the House of Delegates' resolutions. Attached were a number of statements relative to these improvements.